2006
DOI: 10.1126/science.1133904
|View full text |Cite
|
Sign up to set email alerts
|

The Phase-Dependent Infrared Brightness of the Extrasolar Planet ʊ Andromedae b

Abstract: The star upsilon Andromedae is orbited by three known planets, the innermost of which has an orbital period of 4.617 days and a mass at least 0.69 that of Jupiter. This planet is close enough to its host star that the radiation it absorbs overwhelms its internal heat losses. Here, we present the 24-micrometer light curve of this system, obtained with the Spitzer Space Telescope. It shows a variation in phase with the orbital motion of the innermost planet, demonstrating that such planets possess distinct hot s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
208
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(220 citation statements)
references
References 20 publications
(18 reference statements)
7
208
5
Order By: Relevance
“…Harrington et al (2006) reported the first detection of these phase variations for the nontransiting planet υ Andromedae b at 24 μm. If one makes reasonable assumptions about the predicted size and temperature of υ Andromedae b based on its mass and distance from its star, the large size of the observed phase variation implies a large day-night temperature difference and correspondingly inefficient thermal homogenization between the day and night sides.…”
Section: μM Phase Curve For Hd 189733bmentioning
confidence: 99%
“…Harrington et al (2006) reported the first detection of these phase variations for the nontransiting planet υ Andromedae b at 24 μm. If one makes reasonable assumptions about the predicted size and temperature of υ Andromedae b based on its mass and distance from its star, the large size of the observed phase variation implies a large day-night temperature difference and correspondingly inefficient thermal homogenization between the day and night sides.…”
Section: μM Phase Curve For Hd 189733bmentioning
confidence: 99%
“…We note that the relatively homogenized atmospheric temperatures of HD 189733b , contrasted with the large day/night contrasts of HD 179949b (Cowan et al 2007) and υ And b (Harrington et al 2006) seem to reinforce the connection between temperature inversions and larger day/night contrasts. Additional light curve data will be important.…”
mentioning
confidence: 99%
“…In addition to primary transit measurements (Charbonneau et al 2000), these tools include secondary eclipse (Deming et al 2005), differential spectroscopy , phase-curve monitoring (Harrington et al 2006, Cowan et al 2007, Doppler absorption spectroscopy (Snellen et al 2010), and transmission spectra . These observations have motivated many groups to study the atmospheric dynamics of these planets and its role in both redistributing incident stellar energy throughout the atmosphere and (potentially) in influencing the overall evolution of the interior.…”
Section: Introductionmentioning
confidence: 99%